Linux : in a nutshell - Siever, Ellen; Figgins, Stephen; Weber, Aaron (Beijing : O'Reilly, 2003)
Computer Science
Keywords: Linux; Boot method; Red Hat and Debain Package; bash:The bourne-again shell; tcsh:An Extended C Shell; Pattern Matshing; The Emacs Editor; The vi Editor; The sed Editor; The gawk Scripting Language